Construction of vector pcb301-xbxs14-elp and expression of xbxs14 gene coding xylan 1,4- beta-xylosidase from free living bacteria in the gut of termite Coptotermes gestroi in Nicotiana benthamiana by agroinfiltration - Giang, Nguyen Minh; Thu, Nguyen Minh; Duyen, Nguyen Thi; Huyen, Do Thi; Thuong, Ho Thi; Ngoc, Pham Bich; Ha, Chu Hoang; Hai, Truong Nam (Academia Journal of Biology, 2017)
Xylan 1,4-b-xylosidase (EC.3.2.1.37) is one of the important enzymes in lignocellulose degradation. It plays crucial role in the effective xylan degradation into xylose sugar. In this study, the gene Xbxs14 encoding xylan 1,4-b-xylosidase of free-living bacteria in the gut of Coptotermes gestroi termite was successfully cloned into a recombinant pBT vector, and then transferred to fuse with 100x ELPs (Elastin like polypeptide) in the expression vector pCB301-ELP to generate pCB301-Xbxs14-ELP. This recombinant vector was transformed into Agrobacterium tumefaciens bacteria. Using the agroinfiltration method, the gene was introduced into the apoplast of the cells of Nicotiana benthamiana where the transport and delivery of nutrients between and within the cells taking place. Localization of the transformed bacteria into the apoplast will help the interaction and the synthesis of foreign proteins to be effectively preserved. Leaf specimens 6-days after transformation were harvested and crude extract was prepared. Successful expression of soluble xylan 1,4-b-xylosidase in the leaf was confirmed using immunoassay. Crude leaf extracts exhibited xylan 1,4-b-xylosidase activity (4.56 U/g leaves) at the optimum condition of 60oC, pH7. This research provides an important basis to produce xylan 1,4-b-xylosidase from the Xbxs14 gene for the treatment of agricultural waste, paper industry, pharmaceutical and biofuel production.   Citation: Nguyen Minh Giang, Nguyen Minh Thu, Nguyen Thi Duyen, Do Thi Huyen, Ho Thi Thuong, Pham Bich Ngoc, Chu Hoang Ha, Truong Nam Hai, 2017. construction of vector pcb301-xbxs14-elp and expression of xbxs14 gene coding xylan 1,4- beta-xylosidase from free living bacteria in the gut of termite coptotermes gestroi in nicotiana benthamiana by agroinfiltration. Tap chi Sinh hoc, 39(2): 239-248. DOI: 10.15625/0866-7160/v39n2.9843. *Corresponding author: tnhai@ibt.ac.vn Received 25 May 2017, accepted 20 June 2017